The prestige of the pagan prophet Balaam in Judaism, early Christianity and Islam - Kooten, Geurt Hendrik van, 1969-; Ruiten, J. van (Themes in Biblical Narrative, 2008)
This volume deals with the pagan prophet Balaam who figures in the book of Numbers. By the very nature of his stature as a non-Israelite, pagan prophet, the figure of Balaam raises important questions with regard to the nature of prophecy and the relation between the Israelite God and the pagan nations. The conflicting stories and potent oracles of Balaam in Numbers 22-24 and other parts of the Jewish Scriptures prompted extensive reflection on this ambiguous figure. Thus the leading perspective developed in this volume is the often simultaneous praise and criticism of Balaam as a prestigious pagan prophet throughout ancient Judaism, early Christianity and the early Koranic commentaries. The papers are clustered in four sections which deal with (1) Balaam in the Old Testament and the Ancient Near East, and comparable figures in Ancient Greece; (2) Balaam in Ancient Judaism; (3) Balaam in the New Testament andamp; Early Christianity; and (4) Balaam in the Koran and early Koranic commentaries. The reception of this enigmatic figure can be characterized as the simultaneous praise and criticism of a pagan prophet. The book is particularly useful as it also contains Émile Puech's newly reconstructed text, translation and commentary of the first combination of the Deir 'Alla inscriptions which contain an excerpt of the book of the historical Balaam. Combined with the other papers, the volume pictures a fascinating continuum between paganism, Judaism, Christianity, and Islam.